2002
DOI: 10.1029/2002gl015606
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of lateral heterogeneity in the upper mantle around the western Pacific region as inferred from analysis of transverse components of teleseismic P‐coda

Abstract: We investigated the spatial distribution of lateral heterogeneity in the upper mantle in the western Pacific region analyzing transverse components of teleseismic P‐coda recorded by broad‐band seismic networks. Large amplitude transverse components are observed at stations close to plate boundaries such as island arcs for the frequency range of 0.04–2.56 Hz, while small amplitudes are observed at stations on stable continents. Our envelope inversion applied to the observed P‐coda reveals large scattering coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 7 publications
3
11
0
Order By: Relevance
“…Nishimura et al (2002) analyzed the energy partition of teleseismic P-wave and P-coda into the transverse-component to evaluate the lithospheric heterogeneity in the western Pacific region. Nishimura et al (2002) analyzed the energy partition of teleseismic P-wave and P-coda into the transverse-component to evaluate the lithospheric heterogeneity in the western Pacific region.…”
Section: Fig 233mentioning
confidence: 99%
See 2 more Smart Citations
“…Nishimura et al (2002) analyzed the energy partition of teleseismic P-wave and P-coda into the transverse-component to evaluate the lithospheric heterogeneity in the western Pacific region. Nishimura et al (2002) analyzed the energy partition of teleseismic P-wave and P-coda into the transverse-component to evaluate the lithospheric heterogeneity in the western Pacific region.…”
Section: Fig 233mentioning
confidence: 99%
“…Applying the moving window cross-correlation analysis to seismic records from the artificial explosions recorded at eight stations around the focal area, Nishimura et al (2002; found that the average seismic velocity of the crust surrounding the focal region decreased about 1% in the frequency range 3 6 Hz during the three months including the earthquake occurrence. An M 6:1 earthquake took place on the southwestern flank of this volcano on September 3, 1998.…”
Section: Temporal Change In Velocitymentioning
confidence: 99%
See 1 more Smart Citation
“…Korn (1993) further applied this approach to teleseismic P coda observations from nine stations around the Pacific. Nishimura et al (2002) analyzed transverse components in teleseismic P coda for stations in the western Pacific and noted stronger scattering for stations close to plate boundaries compared to those on stable continents. The observed frequency dependence of Q Sc is in approximate agreement with single-scattering theory for random heterogeneities and favors von Karman type ACFs over Gaussian or self-similar models.…”
Section: P Codamentioning
confidence: 99%
“…This method has the merit in that we can evaluate the heterogeneity even at regions where local earthquakes are not observed. Large amplitudes are observed in the transverse component at stations located on active tectonic regions, while small amplitudes are observed on stable continents (Nishimura, 1996;Nishimura et al, 2002;Kubanza et al, 2006Kubanza et al, , 2007. Sato (2006) has formulated the vector waves of P-waves incident to the heteroCopy right c The Society of Geomagnetism and Earth, Planetary and Space Sciences (SGEPSS); The Seismological Society of Japan; The Volcanological Society of Japan; The Geodetic Society of Japan; The Japanese Society for Planetary Sciences; TERRAPUB.…”
Section: Introductionmentioning
confidence: 99%